Uporabnik jezikovnih virov in orodij kot objekt ali subjekt jezikovne politike? – področje prevajanja in tolmačenja - Šorli, Mojca (Slavia Centralis, 2020)
The user of language resources in translation and interpreting: the object or the subject of a language policy? The section on multilingual infrastructure of the Slovenian Language Policy and User Needs CRP 2016 project investigates user habits and attitudes as well as user needs with regard to monolingual and interlingual language resources, in particular, translation technologies, dictionaries and other lexical resources. The research is focused on the needs of translators and interpreters.